Dado o polinômio p(x) = 2x 3 – x 2 + x + 5, o valor de p(2) – p(-1) é:
Soluções para a tarefa
Respondido por
0
Resposta:
15
Explicação passo-a-passo:
P(2) = 2 • 2 • 3 - 2 • 2 + 2 + 5
P(2) = 4 • 3 - 4 + 7
P(2) = 12 - 4 + 7
P(2) = 19 - 4
P(2) = 15
P(-1) = 2 •(-1) • 3 -(-1) • 2 +(-1) + 5
P(-1) = -2 • 3 + 1 • 2 - 1 + 5
P(-1) = -6 + 2 + 4
P(-1) = -6 + 6
P(-1) = 0
P(2) - P(-1) = 15 - 0
P(2) - P(-1) = 15
Perguntas interessantes
História,
10 meses atrás
Matemática,
10 meses atrás
Biologia,
1 ano atrás
Português,
1 ano atrás
Biologia,
1 ano atrás